Difference in ocular surface temperature by infrared thermography in phakic and pseudophakic patients - Sniegowski, Matthew (Clin Ophthalmol, 2015)
PURPOSE: To assess the change in ocular surface temperature between healthy phakic and pseudophakic patients. METHODS: We included patients with no history of ocular disease other than cataract. Patients were divided into three groups: clear lens, cataract, and pseudophakic. All patients had two ocular surface digital thermal scans. An average of five surface points was used as the mean ocular surface temperature. Results were analyzed with a one-way analysis of variance and a Tukey’s least significance difference test. The patients were further divided into phakic and pseudophakic groups. Correlation coefficients between several variables were done in order to assess dependencies. RESULTS: Fifty-six eyes (28 cataracts, 12 clear lenses, 16 pseudophakic) were enrolled. The mean ocular surface temperature in the cataract group was 34.14°C±1.51°C; clear lens: 34.43°C±2.27°C; and pseudophakic: 34.97°C±1.57°C. There were no statistical differences among the study groups (P=0.3). There was a nonsignificant negative correlation trend between age and surface temperature in the phakic group. The trend inverted in the pseudophakic group but without statistical significance. CONCLUSION: Although cataract extraction and intraocular lens implantation seem to induce a mild increase in ocular surface temperature, the effect is not clear and not significant.